An efficient and eco-compatible multicomponent synthesis of 2, 4, 5-trisubstituted imidazole derivatives using modified-silica-coated cobalt ferrite nanoparticles with tungstic acid. Issue 5 (6th January 2023) - Kermanizadeh, Shadan; Naeimi, Hossein; Mousavi, Setareh
Abstract : In this research, a method for green one-pot synthesis of trisubstituted imidazoles using modified-silica coated cobalt ferrite NPs by tungstic acid as catalyst under solvent-free conditions is described. Abstract : The aim of this study has been to offer a method for the synthesis of 2, 4, 5-trisubstituted imidazole derivatives based on green chemistry principles. Therefore, a one-pot multicomponent cyclocondensation reaction through aldehyde interaction with ammonium acetate and 1, 2-diketone under solvent-free conditions was utilized as an eco-effective synthetic route using CoFe2 O4 @SiO2 @(–CH2 )3 OWO3 H NPs as the catalyst. The stabilized tungstic acid on 3-chloropropyl-anchored SiO2 -coated CoFe2 O4 magnetic nanoparticles was designed, prepared, and applied as a recyclable heterogeneous acid catalyst to attain high product yield in a short reaction time. The nanocatalyst structure was confirmed using FT-IR, Raman, XRD, FE-SEM, EDX, VSM, and TGA techniques, and the organic product structures were examined by melting point, FT-IR and 1 H NMR analyses.